Etching dopant elements to construct active-site-rich Mo2C for the hydrogen evolution reaction. Issue 15 (2nd February 2023) - Lu, Qiang; Xiao, Bin; Zhang, Mengling; Sun, Huachuan; Lu, QingJie; Zhou, Tong; Li, Dequan; Deng, Zongming; Xu, Dong; Zhang, Yumin; Zhang, Jin; Liu, Qingju
Abstract : We propose a strategy to etch dopants to construct Mo2 C with more unsaturated coordination of Mo atoms and lattice distortion for enhanced catalytic activity. Abstract : We propose a strategy to etch dopants to construct Mo2 C with more unsaturated coordination of Mo atoms and lattice distortion for enhanced catalytic activity. It is more effective than doping and etching pure Mo2 C and provides a novel strategy for the preparation of catalysts with high catalytic activity.